2018
DOI: 10.3390/w10111523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic Carbon Addition on the Community Structure and Kinetics of Microcystin-Degrading Bacterial Consortia

Abstract: Microcystin (MC), a hepatotoxin that is associated with cyanobacterial blooms in freshwater lakes, threatens the quality of drinking water resources. Biodegradation of MC using biofiltration is emerging as a cost-effective solution for drinking water treatment. This study reports isolation of five MC-degrading microbial consortia and investigation of their community structure and kinetics in the presence or absence of a readily-bioavailable organic carbon source. The results indicated that the presence of a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…and Steroidobacter sp. from drinking water reservoir in Southern California [126] successfully indicated complete MC-LR degradation. Moreover bacterial community isolated from natural waters with previous cyanobacterial contamination was noted to entirely removal MC-LR without lag phase, however, the composition of the bacterial community was not analyzed [134].…”
Section: Biological Degradation By Bacteriamentioning
confidence: 99%
“…and Steroidobacter sp. from drinking water reservoir in Southern California [126] successfully indicated complete MC-LR degradation. Moreover bacterial community isolated from natural waters with previous cyanobacterial contamination was noted to entirely removal MC-LR without lag phase, however, the composition of the bacterial community was not analyzed [134].…”
Section: Biological Degradation By Bacteriamentioning
confidence: 99%
“…The presence of MCs may be responsible for this contrasting outcome of intestinal microbiota succession between the two groups. Some Pseudomonas species and Ralstonia species have been reported to degrade MCs [38,39]. MCs, as an intracellular toxin, are released only after cell death or damage accompanied with cell structure disruption [40].…”
Section: Gut Microbiota Assist B Aeruginosa To Adapt To Toxic Cyanoba...mentioning
confidence: 99%
“…Many studies have found that host exposure to environmental stresses, such as toxic exposure and dietary alterations, does lead to more nodes or more complex interactions of gut flora and even to shifts in the positive and negative relationships between some key bacteria and other bacteria [43][44][45]. Pseudomonas and Ralstonia, as MC-degrading bacteria [38,39], may not only have the ability to increase host tolerance to MCs by themselves, but the co-occurrence network revealed that these bacteria may also influence host resistance to toxic cyanobacterial stress by affecting the entire bacterial community.…”
Section: Gut Microbiota Assist B Aeruginosa To Adapt To Toxic Cyanoba...mentioning
confidence: 99%
“…The bacterial biodegradation of MC-LR has the potential to be an environmentally friendly and cost-effective biotechnology that produces no harmful by-products. Natural bacterial strains or consortia that can effectively degrade MC-LR have been isolated from the natural water. However, biodegradation requires a minimum of 24 h retention time for the complete removal of the toxin, while the hydraulic retention time during biofiltration is much shorter . Therefore, the biodegradation is necessary to be facilitated by capturing toxins on the filtration media to increase the toxin retention time during biofiltration without slowing the water filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%
“… 8 10 However, biodegradation requires a minimum of 24 h retention time for the complete removal of the toxin, while the hydraulic retention time during biofiltration is much shorter. 12 Therefore, the biodegradation is necessary to be facilitated by capturing toxins on the filtration media to increase the toxin retention time during biofiltration without slowing the water filtration efficiency.…”
Section: Introductionmentioning
confidence: 99%